2009
DOI: 10.30552/ejep.v2i2.24
|View full text |Cite
|
Sign up to set email alerts
|

Estimación del aprendizaje matemático mediante la versión española del Test de Evaluación Matemática Temprana de Utrecht

Abstract: El Test de Evaluación Matemática Temprana está orientado a medir el nivel de competencia matemática temprana. Se ha desarrollado para de educación infantil y 1º y 2º de primaria. Dispone de tres versiones paralelas, de 40 ítems cada una. Consta de 8 tareas, divididas en grupos de 5: Comparación, clasificación, correspondencia, seriación, conteo verbal, conteo estructurado, conteo resultante y conocimiento general de los números. Tiene una puntuación máxima de 40 puntos (uno por cada ítem correcto). El objetivo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0
15

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 6 publications
1
3
0
15
Order By: Relevance
“…From the point view of the gradual development of students' skills, results are similar to those obtained with the same instrument in other countries such as England, Finland, Spain and China (Alcalde, Aguilar, Marchena & Ruiz, 2006;Aunio, Aubrey, Godfrey & Liu, 2008;Aunio, Hautamäki, Sajaniemi & Van Luit, 2009;Navarro et al, 2009;Navarro et al, 2010), although it differs from the results obtained in Singapore, a country where studies show a discontinuous development profile. There, scores gradually increase to reach a peak in the curve at 73 months, and then they start to descend (Ee et al, 2006).…”
Section: Discussionsupporting
confidence: 37%
See 2 more Smart Citations
“…From the point view of the gradual development of students' skills, results are similar to those obtained with the same instrument in other countries such as England, Finland, Spain and China (Alcalde, Aguilar, Marchena & Ruiz, 2006;Aunio, Aubrey, Godfrey & Liu, 2008;Aunio, Hautamäki, Sajaniemi & Van Luit, 2009;Navarro et al, 2009;Navarro et al, 2010), although it differs from the results obtained in Singapore, a country where studies show a discontinuous development profile. There, scores gradually increase to reach a peak in the curve at 73 months, and then they start to descend (Ee et al, 2006).…”
Section: Discussionsupporting
confidence: 37%
“…This finding is in line with other research which found that the differences between boys and girls in the early years in mathematics performance are not significant (Klein, Adi-anales de psicología, 2014, vol. 30, nº 3 (octubre) Japha & Hakak-Benizri, 2010;Lachance & Mazzoco, 2006;Navarro et al, 2009;Navarro, Aguilar, Marchena, Alcalde and García, 2010;Van de Rijt, 1996). In Chile, the data provided by national assessments confirm that after the first cycle of elementary education there are no significant differences in achievement levels in mathematics between boys and girls, contrary to what happens at the end of secondary education, when boys have better performance than girls (MINEDUC, 2007b(MINEDUC, , 2007c.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Como instrumento de medición se utilizó el Test de Evaluación Matemática Temprana Utrech (TEMT-U) (Navarro et al, 2009;Navarro, Aguilar, Marchena, Psy, Soc, & Educ, 2011, vol.3, Nº1 Alcalde y García, 2010), que corresponde a la versión española validada del Utrecht Early Numeracy Test, original de Johannes van Luit, bernadette van de rijt y Albèr Pennings, en 1994Pennings, en (van de rijt et al, 1999.…”
Section: Procedimiento E Instrumentosunclassified
“…Del mismo modo que la psicología cognitiva ha descubierto que la clave de la lectura está en la conciencia fonológica, diversos estudios coinciden en que la Competencia Matemática Temprana (CMT) es clave para el aprendizaje de la matemática (Van Luit y Van de Rijt, 2009;Navarro, et al, 2009;Cerda, et al, 2012; Araujo, Aragón, Aguilar, Navarro y Ruiz, 2014).…”
unclassified